Use of Quizizz Education Game Assessment Media Towards Students’ Motivation in Online Learning - Anugrawati, Safitry; Hermansyah, Tatang (International Conference on Elementary Education, 2021)
This study aims to analyze the development of student learning motivation in the online learning process during covid-19 by using a quizizz assessment media. This research is motivated by low student learning motivation, marked by the reduced participation of students in online learning. This assessment was carried out at 243 Cicabe Public Elementary School during distance learning, with a sample of grade VI students. This research is based on the idea that student learning motivation is influenced by many factors, one of which is the use of appropriate assessment media, including quizizz educational game assessment media. This research was conducted using qualitative research with technical analysis with the stages of data reduction, data display, conclusion, and verification. Data collection was carried out using questionnaires and interviews. The questionnaire was made in the form of google form while the interviews were conducted using zoom. The results of the study concluded that the use of quizizz assessment media can develop student learning motivation. Students feel enthusiastic about participating in online learning.